Reform and Empire: The Case of Winnipeg, Manitoba, 1870s–1910s - Korneski, Kurt (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2008)
AbstractDuring the late nineteenth and early twentieth centuries, a host of journalists, ministers, medical doctors, businessmen, lawyers, labour leaders, politicians, and others called for an assault on poverty, slums, disreputable boarding houses, alcoholism, prostitution, sweatshop conditions, inadequate educational facilities, and other “social evils.” Although they represented an array of political positions and advocated a range of strategies to deal with what they deemed problems, historians have come to term this impulse “urban reform” or the “urban reform movement.” Over the past several decades, there have developed two main approaches to the study of this flurry of activity in Canada. Some historians, mostly writing before the mid-1980s, argued that it was an effort to reconstitute “the nation,” which arose in response to the anonymity and social conflict and ills apparent in modern, urban-industrial society. More recently, scholars have emphasized that in Canada reform often preceded urban-industrial development, and that the institutions that reformers supported, like later state agencies, were focused upon moral regulation and in particular fostering and sustaining a liberal order premised on patriarchal concepts of gender and related notions of race. This article demonstrates that important as urban industrial development and moral regulation were, understanding reform in Canada requires the addition of another layer of complexity to already existing analyses. In particular, it shows that we must conceive of Canadian reformers and their institutions as rooted in and shaped by a broader and longer history of European, and particularly British, imperialism.